Analisis Kekuatan Sambungan Baut Yang Searah Dan Melintang Gaya Batang - Paisal Paisal (Jurusan Teknik Mesin, 2023)
The use of bolt joints is widely used in steel structure construction. Because it is easier to handle in construction, it can be disassembled without damage, more varied and more reliable for greater thickness. For the use of bolts that are not too much and the width of the steel plate is not too large, the position of the bolts is usually arranged in an inline position. This study aims to determine the strength of steel joints in line positions with 1 bolt, 2 bolts and 3 bolts with variations in line direction and cros the tensile forces. By conducting a tensile test on two plates connected with bolts with variations in the number and direction of bolts. And the results obtained show that an increase in the number of bolts increases the strength of the joint in linear form relationship according to theory. In a connection with two bolts, the result of a transverse position is obtained a greater stress of 905 MPa compared to the parallel of 904 MPa. And in a connection with three bolts, the result of a parallel position is obtained a greater stress of 1256 MPa than the transverse one of 1215 MPa. Keywords: strength, bolt joint, unidirectional and transverse force